Pooling of Urine Samples for Screening for Neisseria gonorrhoeae by Ligase Chain Reaction: Accuracy and Application - Kacena, Katherine A. (American Society for Microbiology, 1998)
The accuracy of detection of genital Neisseria gonorrhoeae infection in pooled urine samples by ligase chain reaction (LCR) was examined in three populations. Firstly, urine specimens from 300 female military recruits (FMR) were tested by LCR individually and in pools of four and six. Secondly, 300 urine specimens from middle-school students (MSS) were tested individually by LCR, and then the processed specimens were stored frozen for subsequent testing in pools of 4 and 10. Thirdly, 600 frozen urine specimens from high-school students (HSS) were tested by using the LCR pooling algorithm, i.e., testing processed specimens in pools of four in one test unit dose, and retesting individual specimens from positive pools. Finally, the pooling algorithm results were compared to culture results for a subset of 344 students from the original 600 HSS from whom cervical or urethral samples were taken at the discretion of the school nurse practitioners. Compared to individual testing of specimens by LCR in the FMR population, the pooling-by-four algorithm was 100% sensitive (5 of 5) and 100% pool specific (70 of 70), and the pool-by-six algorithm was 100% sensitive (5 of 5) and 100% pool specific (45 of 45). In the MSS population, the pool-by-4 algorithm was 95.8% sensitive (23 of 24) and 100% (52 of 52) pool specific, and the pool-by-10 algorithm was 95.8% sensitive (23 of 24) and 100% (17 of 17) pool specific. In the subset of 344 HSS from whom endocervical or urethral specimens were collected for culture, 31 were positive by LCR in urine and 26 were positive by culture. After results discrepant between culture and LCR were adjudicated by a confirmatory LCR test, the pooling algorithm was 93.8% (30 of 32) sensitive and 99.7% (311 of 312) specific. Culture from these 344 HSS was 81.3% (26 of 32) sensitive. The pooling algorithm reduced the cost of the N. gonorrhoeae LCR assay by 60% compared to individual testing of the HSS specimens and was both sensitive and specific.